2016
DOI: 10.1503/cmaj.151402
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the diagnosis and management of immunoglobulin G4–related disease

Abstract: What pathophysiologic mechanisms are involved in IgG4-related disease? The pathophysiology of IgG4-related disease is uncertain. Both genetic predisposition and environmental triggers may prompt aberrant immune pathways to perpetuate the disease. 15 An overview of current understanding of the disease is shown in Figure 1. 15-23 The pathology seems to be primarily affected by B cells. Patients with IgG4-related disease carry dominantly expanded clones of tissue B cells that produce immunoglobulins with greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 101 publications
1
20
0
2
Order By: Relevance
“…IgG4-related disease (IgG4-RD) is characterized by an increase in IgG4 + cells and circulating IgG4, which is associated with the development of a fibro-inflammatory process mediated by tissue infiltrations of immune cells, including IgG4-positive plasma cells. This process leads to the formation of pseudotumor structures that produce dysfunction or lesions in the affected organs [ 116 , 117 ]. Despite the mechanisms of action involved in this disease remaining largely unknown [ 118 ], some studies have suggested that IL-17 might be implicated in the pathogenesis of the disease.…”
Section: Il-17 In Systemic Rheumatic Diseasesmentioning
confidence: 99%
“…IgG4-related disease (IgG4-RD) is characterized by an increase in IgG4 + cells and circulating IgG4, which is associated with the development of a fibro-inflammatory process mediated by tissue infiltrations of immune cells, including IgG4-positive plasma cells. This process leads to the formation of pseudotumor structures that produce dysfunction or lesions in the affected organs [ 116 , 117 ]. Despite the mechanisms of action involved in this disease remaining largely unknown [ 118 ], some studies have suggested that IL-17 might be implicated in the pathogenesis of the disease.…”
Section: Il-17 In Systemic Rheumatic Diseasesmentioning
confidence: 99%
“…However, as IgG4-RD can be patchy, renal biopsies can on occasion reveal normal histology [ 5 ]. Although no tissue from his aortic aneurysm repair was sent for pathology, his CT chest showed periaortic wall thickening as can be seen in IgG4-related aortitis [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunoglobulin G4-related disease (IgG4-RD) is an immune-mediated multisystem disease that is characterized by inflammation and fibrosis of affected organs [ 1 , 2 ]. Since the disease often presents with nonspecific symptoms and signs and can affect any organ or system, the diagnosis is challenging and often delayed.…”
Section: Introductionmentioning
confidence: 99%
“…The definite diagnosis can be made based on imaging, serology (serum IgG4 > 1.35 g/L) and histology (IgG4+ plasma cells > 10/HPF or IgG4:IgG > 40%). 1 IgG4-related kidney disease usually presents as bilateral multiple renal nodules. 2 The presentation of perirenal soft tissue infiltration is uncommon, but should provoke further histopathologic work-up.…”
mentioning
confidence: 99%
“…Even though there is no conclusive treatment, international consensus suggests giving induction therapy (prednisolone 40 mg/d) with tapering and aiming to stop treatment in three to six months. 1 If treated inadequately, IgG4related disease may cause renal dysfunction and progress to irreversible renal damage. 3…”
mentioning
confidence: 99%